The integrated lot sizing and cutting stock problem in a furniture factory - Vanzela, Matheus [UNESP]; Rangel, Socorro [UNESP]; De Araujo, Silvio A. [UNESP] (Elsevier, 2013)
This work studies the integrated lot sizing and cutting stock problem, where the goal is to capture the dependency that exists between two important decisions in the production process, in order to economize raw materials and also reduce production and inventory costs. The integrated lot sizing and cutting stock problem is studied in a small furniture factory that produces wardrobes, dressing tables and cupboards and the lot sizing and cutting stock decisions are taken by the production manager. A column-generation technique is used to solve a linear relaxation of the proposed model. The computational results, using real data from the factory, show that it is possible to reduce total inventory and raw material costs when integrated planning is used. © 2013 IFAC.
Keywords: Combinatorial optimization; Furniture industry; Lot sizing; Two-dimensional cutting stock; Computational results; Cutting stock problem; Integrated planning; Production and inventory; Production manager; Two-dimensional cutting stocks; Manufacture; Integer programming